Long-term acclimation of anaerobic sludges for high-rate methanogenesis from LCFA - Silva, Sérgio (2014)
Inhibition of methanogens by long chain fatty acids (LCFA) and the low numbers of LCFA-degrading bacteria are limitations to exploit biogas production from fat-rich wastewaters. Generally reactors fail due to excessive LCFA accumulation onto the sludge. Here, long-term acclimation and bioaugmentation with a LCFA-degrading coculture were hypothesized as strategies to enhance methanogenic conversion of these compounds. Anaerobic sludges previously exposed to LCFA for more than 100 days converted a specific biomass-associated substrate of (3.2 ± 0.1) kg·kg−1 with very short lag phases (<1 day), whereas non-acclimated sludges showed lag phases of 11–15 days for metabolizing (1.6–1.8) kg·kg−1. Addition of a coculture of Syntrophomonas zehnderi and Methanobacterium formicicum to sludges previously loaded with LCFA and containing different amounts of biomass-associated substrate (from (0.5–3.2) kg·kg−1) did not improve methane production neither lag phases were shortened, indicating that the endogenous microbiota are not a limiting factor. Clearly, we show that long-term sludge acclimation to LCFA is essential for high rate methanogenesis from LCFA.